A simple and versatile approach to self-healing polymers and electrically conductive composites1. Issue 17 (27th February 2015) - Xie, Tingwan; Zhang, Huan; Lin, Yangju; Xu, Yuanze; Ruan, Yonghong; Weng, Wengui; Xia, Haiping
<x xml:space="preserve">Abstract</x> In this study, a simple and versatile approach to self-healing polymers and electrically conductive composites is reported.